2009
DOI: 10.1182/blood-2009-02-204214
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of congenital acute lymphoblastic leukemia treated on the Interfant-99 protocol

Abstract: Acute lymphoblastic leukemia (ALL) diagnosed in the first month of life (congenital ALL) is very rare. Although congenital ALL is often assumed to be fatal, no studies have been published on outcome except for case reports. The present study reports the outcome of 30 patients with congenital ALL treated with the uniform Interfant-99 protocol, a hybrid regimen combining ALL treatment with elements designed for treatment of acute myeloid leukemia. Congenital ALL was characterized by a higher white blood cell cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(61 citation statements)
references
References 19 publications
3
55
0
3
Order By: Relevance
“…2,7 There was no difference in median age at diagnosis between primary RAS mutationnegative MLL-rearranged infant ALL patients (3.8 months; range 0.0-11.5 months) and the RAS-mutated group (5.3 months; range 0.8-11.8 months) (P=0.89). Likewise, RAS mutations did not seem to affect disease latency when we analyzed t(4;11)-positive infant ALL patients alone.…”
Section: Time Of Disease Onset and Ras Mutationsmentioning
confidence: 94%
See 1 more Smart Citation
“…2,7 There was no difference in median age at diagnosis between primary RAS mutationnegative MLL-rearranged infant ALL patients (3.8 months; range 0.0-11.5 months) and the RAS-mutated group (5.3 months; range 0.8-11.8 months) (P=0.89). Likewise, RAS mutations did not seem to affect disease latency when we analyzed t(4;11)-positive infant ALL patients alone.…”
Section: Time Of Disease Onset and Ras Mutationsmentioning
confidence: 94%
“…3,5 Moreover, in MLL-rearranged infant ALL, short disease latency is strongly associated with a poor clinical outcome. 2,7 Collectively, these inconsistencies form the basis of the question whether MLL fusion proteins (like MLL-AF4) alone are sufficient to induce ALL, or whether these chimeric proteins require co-operative genetic lesions. Bursen et al recently found that not MLL-AF4 but its reciprocal fusion protein AF4-MLL (independent of the presence of MLL-AF4) was capable of inducing pro-B ALL in mice, suggesting that in t(4;11)-positive ALL both fusions may function as co-operative oncoproteins.…”
Section: Introductionmentioning
confidence: 99%
“…My index case expired on the second day of chemotherapy possibly because of leukostasis, coagulopathy or DIC. Two year event free survival and survival of CALL patients treated on the Interfant-99 protocol was 20% [41] but in comparison the outcome of our index case is very much poor because of limited number of case and the baby expired on the day second of chemotherapy.…”
Section: Discussionmentioning
confidence: 77%
“…Combination chemotherapy can achieve remission induction rates in congenital AML similar to those in older infants and children. In congenital ALL, induction failure rates are not significantly different from older infants [3,4]. Herein we report two cases of congenital acute leukemia who presented to our tertiary care hospital.…”
Section: Introductionmentioning
confidence: 99%